Balaghoh Science in Educational Perspective: Innovation in Teaching Methods - Evi Hadi Permana (El-Ma'wa: Journal of Arabic, Translation and Linguistic, 2025)
Balaghah, the study of the beauty and skill of the Arabic language, has great potential for integration into education as an innovative teaching method. This article discusses the implementation of balaghah in an educational context, with the aim of improving students' communication skills and making the teaching and learning process more engaging. Through qualitative field research involving classroom observations, teacher interviews, and student achievement evaluations, it was found that the use of balaghah increased student participation in discussions and presentations, as well as improving their academic performance. The results showed that students were more active and engaged when the balaghah method was applied, which in turn improved their understanding of the subject matter. Furthermore, this article identifies challenges faced in implementing balaghah and provides recommendations for teacher training and curriculum adjustments. Thus, integrating balaghah into education can be a strategic step towards creating a more dynamic and effective learning environment.